Written text production and its relationship to writing processes and spelling ability in persons with post-stroke aphasia. Issue 5 (4th May 2021) - Johansson-Malmeling, Charlotte; Hartelius, Lena; Wengelin, Åsa; Henriksson, Ingrid
ABSTRACT: Background : Writing ability is of increasing importance in our computerised societies, yet research into functional text writing in persons with aphasia (PWA) remains scarce. Knowledge is limited of how different aspects of the writing process interact during writing. Spelling ability has commonly been investigated using dictation tests, but it is not known to what extent those results relate to spelling or editing in text writing. Aims : To compare text writing in the production of narrative texts in persons with and without aphasia and to interrelate measures from the narrative output. Furthermore, to investigate how performance in dictation tasks related to spelling and editing in text. Methods & Procedures : Fifteen participants with mild to moderate aphasia and 26 participants without aphasia in a reference group wrote two types of narratives in a keystroke-logging program and were tested with dictation tests. Writing process measures and characteristics from the texts were compared between groups. Writing process measures were interrelated for both groups. Spelling test results were correlated to spelling and editing in text for the group with aphasia. Outcomes & Results : Significant differences between the two groups were found on all writing process measures; the PWA typed more slowly in the copytask, produced fewer words per minute and deleted a larger proportion of their texts while editing in two narrative tasks. There were also significant differences in text length and the amount of spelling errors in the picture-elicited narrative – but not in the free narrative. There were significant correlations between productivity and editing in both narrative tasks for the group with aphasia, but no such relation was found for the reference group, showing that for the PWA their productivity in text writing aligned with the amount of editing undertaken. A strong correlation between scores on the real-word dictation task and the amount of spelling errors in a picture-elicited text was found, but no correlation was found between scores on the real-word dictation task and spelling errors in the free narrative. Conclusion : All aspects of productivity in text writing were affected in this group of participants with mild to moderate aphasia. There was a relation between editing and production rate for the persons with aphasia, but not for the reference group. Scores on real-word spelling tests cannot predict spelling in free texts for PWA. Editing of writing is time-consuming and problematic for PWA and is worthy of specific focus within assessment and therapy for writing difficulty.